2003
DOI: 10.1111/j.1349-7006.2003.tb01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hepatocyte injury promotes hepatic tumorigenesis in hepatitis C virus transgenic mice

Abstract: Although hepatitis C virus (HCV) is a well-known causative agent of hepatocellular carcinoma (HCC),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Ohata et al 74 recently found that steatosis was independently associated with an increased risk of HCC in chronically infected patients, and some support for this clinical finding is found in animal studies. Transgenic mice expressing HCV viral proteins [75][76][77] have an increased risk of developing hepatocellular adenomas and carcinomas. Steatosis occurs in only some of the models as a viral effect, 75,77 and these animals develop spontaneous tumors in the absence of inflammation.…”
Section: Steatosis Obesity and Primary Liver Cancermentioning
confidence: 99%
“…Ohata et al 74 recently found that steatosis was independently associated with an increased risk of HCC in chronically infected patients, and some support for this clinical finding is found in animal studies. Transgenic mice expressing HCV viral proteins [75][76][77] have an increased risk of developing hepatocellular adenomas and carcinomas. Steatosis occurs in only some of the models as a viral effect, 75,77 and these animals develop spontaneous tumors in the absence of inflammation.…”
Section: Steatosis Obesity and Primary Liver Cancermentioning
confidence: 99%
“…To mimic chronic hepatic inflammation, mice were intraperitoneally injected with 1 ml/kg CCl 4 solution once a week for 12 weeks. Elevated serum ALT levels return to a normal range 4 days after CCl 4 administration in the liver of C57BL/6 mice (Kato et al, 2003). In addition, single i.p.…”
Section: Discussionmentioning
confidence: 92%
“…To induce hepatic injury, mice were intraperitoneally injected with 1 ml/ kg CCl 4 solution (20 v/v% CCl 4 in corn oil) once a week from week 2. The dose and interval of CCl 4 administration were selected based on a study by Kato et al (2003), as conditions to recover from increased levels of serum alanine aminotransferase (ALT) to basal levels. All mice were sacrificed and a part of the left lateral lobe of the liver was preserved with an ISOGEN kit (Nippon Gene, Tokyo, Japan) and stored at -80ºC until used to isolate total RNA.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these models are applied to study relations between carcinogens (like DEN) and HCV-infection in inducing HCC [75,76] . Furthermore, bitransgenic mouse models have been developed to investigate the effect of a particular gene on HCV-induced hepatocarcinogenesis.…”
Section: Hepatitis C Virus-associated Hccmentioning
confidence: 99%